EFEK LANGSUNG DAN RESIDU VERMIKOMPOS PADA PERIODE PENANAMAN KEDUA TERHADAP PERTUMBUHAN DAN HASIL PADA TANAMAN SELADA MERAH (Lactuca sativa L.) DENGAN SISTEM BUDIDAYA TANPA TANAH - muhammad amal firdaus; Nurhidayati Nurhidayati; Abdul Basit (AGRONISMA, 2021)
The aim of this study was to determine the direct and residual effects of vermicompost in the second planting period on the growth and yield of red lettuce with a soilless cultivation system. The research was conducted in a greenhouse which is located at Jl. MT. Haryono 198, Lowokwaru District, Malang City, East Java. The design used was a randomized block design (RBD) with a total of 6 treatments (control (inorganic treatment), 100, 200, 300, 400, and 500 g/pot of vermicompost) repeated 3 times and each treatment had 4 samples. The results of this study showed that the direct effect and residual effect of vermicompost had a significant effect on growth but a dose of vermicompost lower than 500 g/pot was not able to give the same growth as using inorganic fertilizers. The yield of red lettuce at a dose of 500 g/pot of vermicompost gave the highest yield of red lettuce in the second planting period (vermicompost residue effect). Meanwhile, the increase in total plant fresh weight and fresh weight of marketable yield with the highest value was vermicompost treatment of 400 g/pot with an increase of 34.55%.